High Levels of Hemoglobin Promote Carotid Adventitial Vasa Vasorum Neoangiogenesis in Chronic Kidney Disease - Maria Vittoria Arcidiacono; Montserrat Martinez-Alonso; Montserrat Belart; Ana Vilar; Marisa Martín; Lourdes Craver; Àngels Betriu; Dídac Mauricio; José Manuel Valdivielso; Elvira Fernández; Mercè Borràs (Mediators of Inflammation)
Chronic kidney disease (CKD) patients, characterized by traditional and nontraditional risk factors, are prone to develop atheromatosis and thus cardiovascular events and mortality. The angiogenesis of the adventitial vasa vasorum (aVV) surrounding the carotid has been described as the atheromatosis initiator. Therefore, the aim of the study was to (1) evaluate if the carotid aVV in CKD patients increases in comparison to its physiological value of healthy patients; (2) explore which traditional or nontraditional risk factor including inflammation, bone and mineral metabolism, and anemia could be related to the aVV angiogenesis. CKD patients without previous cardiovascular events (44, stages 3-4; 37, stage 5D) and 65 healthy subjects were compared. The carotid aVV and the intima-media thickness (cIMT) were evaluated by ultrasound. CKD patients at stages 3-4 showed higher aVV of the right carotid artery even after adjusting for age. Importantly, a multiple linear regression model showed hemoglobin levels > 12.5 g/dL as the factor for an estimated higher aVV of the right carotid artery. In conclusion, the association of hemoglobin with higher aVV could suggest the role of high hemoglobin in the higher incidence of adverse cardiovascular outcomes in CKD patients.